Microglia and Microglia-Like Cells: Similar but Different - Cuadros, Miguel A.; Sepulveda, M. Rosario; Martin-Oliva, David; Marín-Teva, José L.; Neubrand, Veronika E. (Frontiers in Cellular Neuroscience, 2022)
Microglia are the tissue-resident macrophages of the central nervous parenchyma. In mammals, microglia are thought to originate from yolk sac precursors and posteriorly maintained through the entire life of the organism. However, contribution of microglial cells from other sources should also be considered. In addition to “true” or “bona-fide” microglia, which are of embryonic origin, the so-called “microglia-like cells” are hematopoietic cells of bone marrow origin that can engraft the mature brain mainly under pathological conditions. These cells implement great parts of the microglial immune phenotype, but they do not completely adopt the “true microglia” features. Because of their pronounced similarity, true microglia and microglia-like cells are usually considered together as one population. In this review, we discuss the origin and development of these two distinct cell types and their differences. We will also review the factors determining the appearance and presence of microglia-like cells, which can vary among species. This knowledge might contribute to the development of therapeutic strategies aiming at microglial cells for the treatment of diseases in which they are involved, as for example neurodegenerative disorders like Alzheimer´s and Parkinson´s diseases.